Predictive risk factors for distant metastasis in pediatric differentiated thyroid cancer from Saudi Arabia - Parvathareddy, Sandeep Kumar; Siraj, Abdul K.; Annaiyappanaidu, Padmanaban; Siraj, Nabil; Al-Rasheed, Maha; Al-Haqawi, Wael; Qadri, Zeeshan; Siddiqui, Khawar; Al-Sobhi, Saif S.; Al-Dayel, Fouad; Al-Kuraya, Khawla S. (Frontiers in Endocrinology, 2023)
Background: Despite their excellent prognosis, children and young adults (CAYA) with differentiated thyroid cancer (DTC) tend to have more frequent occurrence of distant metastasis (DM) compared to adult DTC. Data about DM in CAYA from Middle Eastern ethnicity is limited. Methods: Medical records of 170 patients with DTC ≤18 years were retrospectively reviewed. Clinico-pathological factors associated with lung metastasis in CAYA, their clinical presentation and outcome were analyzed. Rick factors related to distant metastasis-free survival (DMFS) for the whole cohort were evaluated. Results: DM was observed in 27 patients and all were lung metastasis. Lung metastasis was significantly associated with younger age (≤15 years), extrathyroidal extension, multifocal tumors, bilaterality, presence of lymph node (LN) disease and high post-operative stimulated thyroglobulin (sTg). Highest negative predictive values were seen with low post-operative sTg (97.9%), absence of LN disease (95.2%), absence of ETE (92.2%) and age older than 15 years (92.9%). Post-therapy whole body scan (WBS) identified most of the lung metastasis (21 of 27; 77.8%). Upon evaluating patients response according to ATA guidelines, excellent response was seen in only one patient, while biochemical persistence and structural persistence were seen in 11.1% (3/27) and 77.8% (21/27), respectively. Elevated post-operative sTg (>10ng/ml) was the only risk factor found to be significantly associated with both biochemical persistence (with or without structural persistence (p = 0.0143)) and structural persistence (p = 0.0433). Cox regression analysis identified age and postoperative sTg as independent risk factors related to DMFS. Based on these two risk factors for DMFS, patients were divided into 3 groups: low risk (no risk factors), intermediate risk (1 risk factor) and high risk (both risk factors). 20-year DMFS rates in the low-, intermediate-and high-risk groups were 100.0%, 81.3% and 23.7% respectively (p < 0.0001). Conclusion: Higher suspicion for metastatic pediatric DTC should be considered in patients who are young, have LN disease, extrathyroidal extension and elevated postoperative sTg. Persistent disease, despite therapy, is very common and it appears to be related to post-operative sTg level. Hence, risk adaptive management is desirable in CAYA with DTC.